2007
DOI: 10.1111/j.1365-3016.2007.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene theory and allergy and asthma prevention

Abstract: Summary Epidemiological trends of allergic diseases and asthma in children reveal a global rise in their prevalence over the past 50 years. Their rapid rise, especially in metropolitan locales, suggests that recent changes in modern environments and/or life styles underlie these trends. One environmental/life style factor that may be contributing to this trend is called the hygiene hypothesis: that naturally occurring microbial exposures in early life may have prompted early immune maturation and prevented all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…Although this was not the primary aim of the analyses, this finding is consistent with several studies linking lower SES to lower incidence of allergic asthma [31,32,44,45]. Although controversial, it has been suggested that this relationship may be due to the "hygiene hypothesis," which proposes that the development of atopic asthma and allergy may be prevented via prenatal and-or early childhood exposure to immune system stimulants (e.g., bacteria, viruses and endotoxins) that shift T-helper type 2 cell (Th2) dominance to T-helper type 1 cell (Th1) dominance [46,47]. This shift in cytokine balance is thought to contribute to allergic asthma and allergy, and may be induced by a lack of early exposures to microbial environments [46], which are typical in lower SES settings (e.g., poor housing conditions that may be overcrowded, infested with cockroaches and dust mites, and poorly insulated, leading to greater exposure to infections, allergens, and mould).…”
Section: Discussionmentioning
confidence: 99%
“…Although this was not the primary aim of the analyses, this finding is consistent with several studies linking lower SES to lower incidence of allergic asthma [31,32,44,45]. Although controversial, it has been suggested that this relationship may be due to the "hygiene hypothesis," which proposes that the development of atopic asthma and allergy may be prevented via prenatal and-or early childhood exposure to immune system stimulants (e.g., bacteria, viruses and endotoxins) that shift T-helper type 2 cell (Th2) dominance to T-helper type 1 cell (Th1) dominance [46,47]. This shift in cytokine balance is thought to contribute to allergic asthma and allergy, and may be induced by a lack of early exposures to microbial environments [46], which are typical in lower SES settings (e.g., poor housing conditions that may be overcrowded, infested with cockroaches and dust mites, and poorly insulated, leading to greater exposure to infections, allergens, and mould).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies were in developed countries, yet, asthma phenotypes and, the role and extent of the factors associated with asthma differ in developed and low-income countries [8,9]. Research has also indicated that, the role of some factors associated with asthma such as exclusive breastfeeding and early exposure to infection is controversial [10-12]. …”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that failure to develop a balanced immune response plays a key role in asthma and allergy development [1], [2], [3], and that environmental microbial exposure and host sampling of the developing gastrointestinal (GI) microbial community over the first year of life are crucial to immune response maturation [4], [5]. Culture-based approaches have suggested that the development of the GI microbiome is a progressive event beginning at birth and continuing until infants are weaned, with particular organisms acquired in distinct phases [6].…”
Section: Introductionmentioning
confidence: 99%